Melanotic neuroectodermal tumour of infancy. - Siddiqui, TH; Amin, MR; Bashar, MA; Ahmed, Z; Matin, A; Hasan, GZ; Islam, MD; Hossain, MZ (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 287-291 The abstract of this article is available on the PubMed website